Translanguaging for Empowerment and Equity Language Practices in Philippine Education and Other Public Spaces - Canilao, Maria Luz Elena Nabong; De Los Reyes, Robin Atilano (Springer Nature Singapore : Imprint: Springer, 2023)
XXII, 278 p. 43 illus., 24 illus. in color.